COMPOSITE-INDICATORS FOR URBAN ECOSYSTEM SERVICES AT SITE-LEVEL: A SYSTEMATIC LITERATURE REVIEW - Barbosa, Valéria Letícia Marques; de Faria, Luiz Carlos; Cardoso-Leite, Eliana (Revista da Sociedade Brasileira de Arborização Urbana, 2024)
Urban green areas, crucial components of green infrastructure, provide a variety of ecosystem services (ES) essential for enhancing the quality of life in cities. The quantity and quality of these ES are estimated and evaluated using indicators that serve as urban planning tools. However, these indicators are often challenging to generalize as they have been developed for specific locations and situations, frequently focusing on just one dimension - ecological, environmental, or economic. In this context, this study explored indicators for ES in urban green areas found in scientific articles from Scopus, Web of Science, and Scielo, through a Bibliometric Analysis and Systematic Literature Review following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Upon thorough examination of the 37 articles resulting from PRISMA, a predominance of indicators related to regulating services, particularly in urban parks, followed by cultural and supporting services, was observed. A diversity of indicators, methodologies, and analysis frameworks for ES was identified without a clear standardization, potentially complicating their application in urban green infrastructure planning and management. A research gap was noted regarding ES indicators studies in tropical and subequatorial urban environments, especially those that establish connections between ES and the necessary innovations to promote them.